Geometric and numerical optimal control : application to swimming at Low Reynolds number and magnetic resonance imaging /: application to swimming at Low Reynolds number and magnetic resonance imaging. (2018) - Bonnard, Bernard, 1952-; Chyba, Monique, 1969-; Rouot, Jérémy
No abstract available